Disclosure of R&D activities - Silva, S. M. T. (2016)
The aim of this study is to investigate whether the dissemination of information about Research and Development (R&D) in Sweden and Finland has increased upon the adoption of International Accounting Standard no. 38 (IAS 38) for companies listed on the “Stockholm Stock Exchange” and the “Helsinki Stock Exchange”, and also to identify the determinants of these disclosures. The sample is composed of 36 companies that were analyzed over the period between 2005 and 2008. Results in general show that the companies not only reported the information required by IAS 38, but also made voluntary disclosures about these activities. With regard to the determinants of disclosure the following conclusions were drawn: the variables such as company size, debts, kind of auditor, internationalization, and sector of activity are statistically significant for the “Required Disclosure Index” dependent variable, while the variables such as company size, debts, profitability, sector of activity, and country are statistically significant for the “Index of Voluntary Disclosure” dependent variable.